Práticas e representações de leitura literária no Ifes/Campus de Alegre: uma história com rosto e voz - Valtão, Rosana Carvalho Dias (2016)
Inserted in a context marked by the spread of the idea that literary reading is in crisis and that the youth of the XXI century read less and less; and starting from the premise that reading is a practice that happens to exist in contextualized spaces, with different gestures and habits in each age, the study "Practices and representations of literary reading at Ifes/Campus Alegre: a story with face and voice" investigated how literary reading happens in this educational institution (Ifes/Campus Alegre), mapping in what reader context the social group of students of that institution is located, what are their strategies, methods, practices, and representations of reading and how the studied people appropriate of what they read in and outside the school. For this, this research spoke to the work of the French historian Roger Chartier and the epistemological principles of Cultural History, regarding to the history of books, reading and literature. In the developing of this study we carried out the bibliographic and documentary, and field research, in a qualitative perspective, using the deductive method. Considering the principle that every cultural reality is built on the relationships between social groups, we found the existence of a practice of reading that disengages the work with reading literature in the classroom. Have been identified, although, the modalities shared reading of the present readers communities in the studied context: we realize that the main access roads and ways of acquiring the cultural object (literature book) happen through loans and exchanges among students and we found that their peers are the main mediators of existing literary reading in this space. These results allowed us to trace a literary reading profile Ifes / Campus Alegre.